2010
DOI: 10.1002/14651858.cd001706.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasties (with and without bone cement) for proximal femoral fractures in adults

Abstract: Analysis 1.1. Comparison 1 Cemented versus uncemented prosthesis, Outcome 1 Length of surgery (minutes). . . Analysis 1.2. Comparison 1 Cemented versus uncemented prosthesis, Outcome 2 Operative blood loss (ml). . . . Analysis 1.3. Comparison 1 Cemented versus uncemented prosthesis, Outcome 3 Mean units blood transfused. . . Analysis 1.4. Comparison 1 Cemented versus uncemented prosthesis, Outcome 4 Peri-operative death. . . . . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
130
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 34 publications
2
130
2
1
Order By: Relevance
“…The Cochrane Review published in 2010 concluded that patients with cemented HA experienced less pain at one year or later and had improved post-operative mobility compared with patients having uncemented HA, while mortality and surgical complications were not significantly different between these groups [26]. A recent systematic review concluded that cemented HA reduces the risk of residual pain and provides better functional outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Review published in 2010 concluded that patients with cemented HA experienced less pain at one year or later and had improved post-operative mobility compared with patients having uncemented HA, while mortality and surgical complications were not significantly different between these groups [26]. A recent systematic review concluded that cemented HA reduces the risk of residual pain and provides better functional outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Others, such as Calder et al [1] in a study on 250 patients, Cornell et al [2] in a study including 48 patients, Davison et al [3] reporting on 187 patients and finally Raia et al [4] in a study including 115 patients, also failed to present differences in clinical outcome or surgical complications when comparing uni-and bipolar HAs in randomised studies. Subsequently, a Cochrane review from 2010 based on the seven studies published so far concluded that there is currently not enough evidence to support the use of either unipolar or bipolar prosthesis when performing an HA [12].…”
Section: Discussionmentioning
confidence: 99%
“…In bipolar hemiarthroplasty for displaced femoral-neck fractures in elderly patients, the evidence suggests that both traditional and modern cemented prostheses provide more favorable clinical outcomes than do uncemented implants [4,5,7]. Cemented hemiarthroplasty has a significantly lower rate of intraoperative and postoperative implant-related complications [6].…”
Section: Discussionmentioning
confidence: 99%
“…Hemiarthroplasty has a better functional outcome and fewer complications than internal fixation for the treatment of displaced femoral-neck fractures in elderly patients [2][3][4]. There are many different prostheses available for hemiarthroplasty, but the optimal technique remains controversial [4]. For example, it is unclear whether cemented or uncemented implants are preferable in this patient population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation